The Effect of Retinoic acid on blood vessel of chicken embryos - Eman A. Alsageer; saad, kawakeb (Surman Journal of Science and Technology, 2025)
Formation of the vasculature is an essential developmental process, delivering oxygen and nutrients to support cellular processes needed for tissue growth and maturation. Retinoic acid (RA) and its downstream signaling pathway is vital for normal pre- and post-natal development, playing key roles in the specification and formation of many organs and tissues, Exogenous of RA can cause malformation in these organs and tissues. The current study aimed to find out the effect of application of different concentrations 1.5, 6 ,10mg/ ml of retinoic acid dissolved in dimethyl sulphoxide (DMSO) on chicken blood vessels development at different embryonic stages. Domestic fertile Gallus gallus After being cleaned and sterilized, eggs from a nearby poultry farm were split into two experimental groups, one for each concentration. Three groups of ten eggs each are used in each experiment. These groups repeated four time for four different stages HH8, HH10, HH15 and HH18After being incubated for the necessary of required time, the eggs were taken out and then either injected with RA or DMSO in an air sac or left untreated as a control. They were then incubated for an additional twenty-four hours. Eggs were opened after 24 and 48 h of incubation, surviving embryos were collected and blood vessels formation were evaluated morphologically. The results of this study showed that RA causes general growth retardation of blood vessels. The degree of malformation depended on the developing stage and RA concentration, where malformation increases with high concentration and early stages.